The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1101/2021.05.20.21257537
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lockdown babies- Birth and new parenting experiences during the 2020 Covid-19 lockdown in South Africa

Abstract: Background Perceived birth experiences of parents can have a lasting impact on children. We explored the birth and new parenting experiences of South African parents during the Covid-19 lockdown. Methods We conducted an online cross-sectional survey with consenting parents of babies born in South Africa during 2020. Factors associated with negative birth emotions and probable depression were estimated using logistic regression. Results Most of the 520 respondents were females (n= 496, 95%) who gave birth at … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…In South Africa, the COVID-19 lockdown led to mothers reporting delays in registering their babies. Only a third of the mothers saw a lactation consultant in the hospital during lockdown compared to the period before lockdown with only 14% of mothers who delivered during the lockdown reporting accessing professional support for mental health post-delivery [25] . One study conducted in Kenya revealed no differences in the utilization of immunization services during the COVID-19 pandemic [19] .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In South Africa, the COVID-19 lockdown led to mothers reporting delays in registering their babies. Only a third of the mothers saw a lactation consultant in the hospital during lockdown compared to the period before lockdown with only 14% of mothers who delivered during the lockdown reporting accessing professional support for mental health post-delivery [25] . One study conducted in Kenya revealed no differences in the utilization of immunization services during the COVID-19 pandemic [19] .…”
Section: Resultsmentioning
confidence: 99%
“…Of the included studies, five were conducted in Ethiopia [11] , [13] , [14] , [15] , [16] , three in Kenya [17] , [18] , [19] , two in Nigeria [20] , [21] , and one each in the Democratic Republic of Congo [22] , Mozambique [23] , Rwanda [24] , South Africa [25] and Uganda [26] . Four were multi-country studies [27] , [28] , [29] , [30] .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations